The Perceptions of Panaboan Entrepreneur about Sustainable Development Goal (SDG) #13 Climate Action - Bedico, Hannah Joy C.; Corbeta, Angelica D.; Cruz, Roigheena P. Dela; Allawan, Jovany Gleen (Universitas Brawijaya, 2024)
This study searched a deeper understanding of the perceptions of entrepreneurs about sustainable development goal (SDG) #13 climate action in Panabo City, Philippines. Purposive sampling was used which included six participants to answer the given questions and who are entrepreneurs residing in Panabo City, Davao del Norte. The participants are undergoing an in-depth interview with ages 25 to 40 years old with at least one year in their business, gender, and civil status. This study utilized a qualitative approach, particularly phenomenological study design through the use of a validated in-depth interview questionnaire. Furthermore, the results show reducing emissions, sustainability, and environmental government policies. The participants shared their perceptions about sustainable development goal #13 climate action to their business. Finally, implications of what indicators to create to address the Panaboan entrepreneurs.